Obstetric antiphospholipid syndrome: An approach from glycans of the immunoglobulin G - Angela Maria Alvarez; Alejandra Maria Gomez-Gutierrez; Julio Cesar Bueno-Sanchez; Carolina Rua-Molina; Angela Patricia Cadavid (Journal of Human Reproductive Sciences, 2021)
This is a case report of women with pregnancy morbidity (PM), some of them associated with antiphospholipid syndrome (APS), in which the glycan patterns of immunoglobulin G (IgG) were investigated based on the theory of alteration of glycosylation in autoimmunity. We used lectin blot to determine changes in terminal glycosylation of polyclonal IgG from women with antiphospholipid (aPL) antibodies and PM plus vascular thrombosis (PM/VT) and seronegative-obstetric APS (SN-OAPS). In addition, we analyzed IgG from women with PM without aPL (PM/aPL-) and healthy women, as controls. Even though the SN-OAPS and PM/VT groups share the PM, only the SN-OAPS group showed a decreased expression of galactose compared to the healthy group. We also found the presence of mannosylated oligosaccharides in IgG from all patients being significantly higher in IgG from women of the PM/aPL- group. The differences in glycans presented here could relate to pathological mechanisms of PM associated with APS.